Place-Consciousness and Bronfenbrenner’s Ecological Systems Model: A Discussion of Recurring Issues that Undermine the Teaching of Indigenous Histories in New Zealand and Australian Schools - Manning, Richard F. (The Australian Journal of Indigenous Education, 2017)
This article draws upon a ‘tale from the field’ (Van Maanen, 1988) to encourage New Zealand and Australian teachers of history and social studies to appraise how their own perceptions of place and teaching about Indigenous peoples’ histories impact upon their students’ learning. Moreover, it explains why Uri Bronfenbrenner's (1979) ecological systems model (despite its limitations) can assist the process of critiquing the teaching of Indigenous histories in schools on both sides of the Tasman Sea. It concludes that place conscious Indigenous land-based learning experiences, resulting from mutually beneficial collaborations with Indigenous communities, are needed to enhance the teaching of Indigenous peoples’ histories in both countries.